ANALISIS DAN PERANCANGAN SISTEM INFORMASI PADA PT MAJA AGUNG ELEKTRINDO - Yoshua Christianto (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
The purpose of this system analysis and design is to find the problems and weaknesses that exist in the company and designing a new information system to support all activities of the company. The old system in the company is still run manually that causes recording errors, calculation errors, difficulty in accessing the data, data loss, and reduce the quality of the information needed by the company for decision making. The methodology used in this system analysis and design is SDLC (System Development Life Cycle) method which consists of a planning and selection phase, analysis phase, design phase, implementation and operation phase. This system analysis and design be able to manage the sales, purchasing, finance processes, warehousing data, employee data, and production data with computerized data management and a database. Key words Computerized system, Database, Information system, System analysis and design.